2006
DOI: 10.1097/01.shk.0000196548.10634.02
|View full text |Cite
|
Sign up to set email alerts
|

Oral Glutamine Enhances Heat Shock Protein Expression and Improves Survival Following Hyperthermia

Abstract: No pharmacologic agent has shown benefit in treating heatstroke. Previous data indicate that enhanced heat shock protein 70 (HSP-70) expression can improve survival postexperimental heatstroke. Glutamine (GLN) can enhance HSP-70 expression in other injury models. This study assessed if orally administered GLN could enhance tissue HSP expression and could improve survival following whole body hyperthermia. Intestinal permeability and plasma endotoxin were assayed to determine if enhanced HSP expression correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
101
1
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(111 citation statements)
references
References 31 publications
2
101
1
7
Order By: Relevance
“…Numerous authors have reported that environmental stressors affect intestinal barrier integrity, which is composed of enterocytes, tight junctions, secreted mucous and immune cells, such as macrophages (Lambert et al, 2002;Prosser et al, 2004;Singleton & Wischmeyer, 2006;Chappell et al, 2009;Lambert, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous authors have reported that environmental stressors affect intestinal barrier integrity, which is composed of enterocytes, tight junctions, secreted mucous and immune cells, such as macrophages (Lambert et al, 2002;Prosser et al, 2004;Singleton & Wischmeyer, 2006;Chappell et al, 2009;Lambert, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The modified fat component is formulated to be similar to typical North American dietary patterns in humans (40% of calories, polyunsaturated/saturated fat ratio of 0.35; Savarese et al (10) reviewed the possible prevention of chemotherapy toxicity by glutamine. Because several recent studies have shown that glutamine bolus treatment rescued rats from lethal endotoxin shock or hyperthermic stress (22,23), we opted for the bolus dose used in those investigations (0.75 g/kg/d). Other experimental treatments were incorporated in the diet (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, therapeutic strategies that maintain intestinal TJ barrier function during HS are being actively pursued as an important therapeutic option in heat stroke. 24,25,28 Previous studies from our laboratory indicated that a physiologically relevant increase in temperature (39°C or 41°C) causes an increase in occludin protein expression and an increase in junctional localization. 29,30 The increase in junctional localization of occludin has been postulated to be an important protective mechanism against HS-induced disruption of TJ barrier in intestinal epithelial monolayers.…”
mentioning
confidence: 99%